DIFFERENCE IN GLICATED HEMOGLOBIN LEVEL BETWEEN BORONATE AFFINITY METHOD AND ION EXCHANGE-HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD IN TYPE 2 DIABETES MELLITUS - Tuti Asryani; Ellyza Nasrul; Rikarni Rikarni; Tutty Prihandani (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Background: Glycated Hb (HbA1c) test is needed to control glycemic in high prevalence type 2 diabetes mellitus (DM) patients. Hemoglobin fraction separated and chemical reaction are two main concepts in HbA1c test. Ion exchange-high performance liquid chromatography (HPLC) and boronate affinity use first concept. Ion exchange-HPLC is reference method in most of clinical laboratorium. Point of care testing (POCT) with boronate affinity method that has been standardized by international institution is available. The aim of this study was to compare boronate affinity POCT method and ion exchange-HPLC method.Method: This cross sectional study was conducted to 22 type 2 DM patients those fullfill inclusion and exclusion criteria in January 2017 to February 2018. Level of HbA1c was assayed with boronate affinity POCT and ion exchange-HPLC method. T-test was used to analyse data and no significance difference if p>0.005Results: Subjects of this study are women (59.1%) more than men (40.9%) with age mean 59.23 years old (8.1). Uncontroled type 2 DM (77.3%) more than controled type 2 DM (22.7%).Mean of HbA1 level was 8.0% (1.7) in boronate affinity POCT and 8.3% (1.8) in ion exchange-HPLC. T-test showed no significance difference between those two HbA1C assay methods (p>0.005).Conclusion: There was no difference HbA1c level between boronate affinity POCT method and ion exchange-HPLC method.